PROCESSING GNDVI AND CVI SPECTRAL INDICES BASED ON DISTANCE SCOMING DATA - Seitnazarov, K.K.; Madirimova, S.M.; Turemuratova, B.K.; Aitmuratov, B.B. (SCIENCE and SOCIETY, 2026)
This article focuses on the computation of the GNDVI and CVI vegetation indices, which exhibit high sensitivity to vegetation condition, particularly to chlorophyll content. It is also noted that the module architecture is based on a pipeline approach, which ensures modularity, scalability, and robustness in the processing of large volumes of satellite imagery. The implementation includes computational optimization as well as integration with a geospatial PostgreSQL/PostGIS database.